2019
DOI: 10.1111/bph.14639
|View full text |Cite
|
Sign up to set email alerts
|

The MC4 receptor agonist RO27‐3225 inhibits NLRP1‐dependent neuronal pyroptosis via the ASK1/JNK/p38 MAPK pathway in a mouse model of intracerebral haemorrhage

Abstract: Background and Purpose: Inflammasome-mediated pyroptosis is an important neuronal cell death mechanism. Previous studies reported that activation of melanocortin MC 4 receptor exerted neuroprotection in several neurological diseases. Here, we have investigated the role of MC 4 receptor activation with RO27-3225 in suppressing neuronal pyroptosis after experimental intracerebral haemorrhage (ICH) and the underlying mechanism.Experimental Approach: One hundred and sixty-nine male CD1 mice were used. ICH was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 62 publications
1
42
0
Order By: Relevance
“…Three different formats of Kremen-1 siRNA or DVL-1 siRNA (OriGene Technologies, MD, USA) were diluted with transfection reagent (EntranserTM, Engreen Biosystem). ICV administration was performed at 24 h before ICH as described [32][33][34]. The Kremen-1 siRNA, DVL-1 siRNA, and scramble siRNA mixture (100 pmol in 2 μl) was delivered into the ipsilateral ventricle, administration at a rate of 0.667 μl/min.…”
Section: Drug and Sirna Administrationmentioning
confidence: 99%
“…Three different formats of Kremen-1 siRNA or DVL-1 siRNA (OriGene Technologies, MD, USA) were diluted with transfection reagent (EntranserTM, Engreen Biosystem). ICV administration was performed at 24 h before ICH as described [32][33][34]. The Kremen-1 siRNA, DVL-1 siRNA, and scramble siRNA mixture (100 pmol in 2 μl) was delivered into the ipsilateral ventricle, administration at a rate of 0.667 μl/min.…”
Section: Drug and Sirna Administrationmentioning
confidence: 99%
“…Double fluorescence staining was performed as described previously [ 16 ]. Sections were blocked with 5% donkey serum for 1 h and incubated at 4 °C overnight with primary antibodies: rabbit anti-RXFP1 (1:100, Biorbyt, orb157275), mouse anti-tryptase (1:200, Abcam, ab2378), mouse anti-chymase (1:200, Santa Cruz, sc-59586), and rabbit anti-TNFAIP3 (1:100, Lifespan, LS-C352948) followed by incubation with appropriate fluorescence-conjugated secondary antibodies for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, studies have suggested that melanocortins are safe and effective candidates for treating subarachnoid hemorrhage- and intracerebral hemorrhage- related complications [ 125 , 126 ].…”
Section: Anti-inflammatory Effects Of α-Mshmentioning
confidence: 99%